Ranking and Analyzing the Stability Status of Rural Settlements (Case Study: Zarrindasht County) - Mohsen Shayan; Dr.Siroos Ghanbari; Dr.Javad Bazrafshan (جغرافیا و آمایش شهری منطقه‌ای, 2018)
Nowadays sustainable development approach as a framework for analyzing sustainability of human settlements’ System in general and rural settlements as  particularly are  highly valued. Assessment and analysis capabilities of rural areas and bottlenecks in rural development planning process is very important. In this regard purpose of this research is the investigation and analysis of the sustainability status in rural settlements of Zarrindasht County. In the research process, the theoretical foundation of sustainability assessment and the studies  records  were studied. According to the information available in the study area, 78 indicators  of stability in five economic, social, environmental, physical, and access was determined. The statistical population of the  study involved heads of rural households (7927) and experts. Among the first group, 310 questionnaires were sampled using Cochran's formula in a simple random sample of 30 sample size experts. In this study ] to analyze the quantitative data of single-sample t-test and to obtain dimensions and weight of each priority districts of fuzzy hierarchical analysis is used. The results show that the district Khosuyeh with weigh 0.354 as the most stable district it has been found in five dimensions. District Zirab with weigh 0.247 weak sustainability, district West Izadkhast with weigh 0.153 in terms of metastable and also  East Izadkhast with weigh 0.072 and district Dabiran with weigh 0.077 as the most unstable district of the city have been selected. Also, the results of one-sample t-test show that Khoshiva's district with the average of 3.629 has the highest mean and the Dabiran district has the lowest average of 2.516.